Educating Orang Asli students: the challenges towards achieving the Malaysian sustainable education agenda / Intan Waheedah Othman - Othman, Intan Waheedah (Universiti Teknologi MARA, Perlis, 2022)
A low participation of the Orang Asli students can be seen in the local education system and has persisted even after decades of study and enforcement of several government policies. This paper reviews prior research on Indigenous education, to determine how the Orang Asli students are impacted by the mainstream educational curriculum. In attaining the Sustainable Development Goals (SDG) vision of "Education for All" and ensuring that the indigenous students succeed in school, this paper is of the view that it is crucial that a culturally compatible curriculum is implemented in schools. Besides, teachers may need to tailor their teaching style to the Orang Asli students' needs to allow a more enhanced learning outcome while retaining their cultural competence.